2015
DOI: 10.1016/j.dcn.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The functional foetal brain: A systematic preview of methodological factors in reporting foetal visual and auditory capacity

Abstract: Due to technological advancements in functional brain imaging, foetal brain responses to visual and auditory stimuli is a growing area of research despite being relatively small with much variation between research laboratories. A number of inconsistencies between studies are, nonetheless, present in the literature. This article aims to explore the potential contribution of methodological factors to variation in reports of foetal neural responses to external stimuli. Some of the variation in reports can be exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 45 publications
2
26
0
1
Order By: Relevance
“…During avian development, as a consequence of embryo orientation in the egg, differential exposure to light for the left or right eye due to the location of the wing results in brain lateralization in chicks [21]. Multiple studies have investigated the response of the human fetal brain to light [22], although none have delivered stimuli that have contained the percept of an image. This absence has been driven by the complexity of delivering visual stimuli to the fetus.…”
Section: From Prenatal To Postnatal Visual Developmentmentioning
confidence: 99%
“…During avian development, as a consequence of embryo orientation in the egg, differential exposure to light for the left or right eye due to the location of the wing results in brain lateralization in chicks [21]. Multiple studies have investigated the response of the human fetal brain to light [22], although none have delivered stimuli that have contained the percept of an image. This absence has been driven by the complexity of delivering visual stimuli to the fetus.…”
Section: From Prenatal To Postnatal Visual Developmentmentioning
confidence: 99%
“…Language development starts in utero based on prenatal exposure to speech. Indeed, by 33–34 weeks of gestation, functional MRI suggests that the fetal brain shows neural activation to speech sounds (see Dunn, Reissland, & Reid, for review; Jardri et al., , ). At birth, neonates activate a similar network of temporal and frontal regions as observed in adults in response to speech stimuli (Perani et al., ; Sato et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to light diffusion, even if the previously unreported assumptions of Scheel et al [1] were correct, and the published model [3] used by Reid et al [2] was not, the two conditions presented by Scheel et al [1] nonetheless differentially deliver stimuli with variation between upper and lower visual fi eld. It is likely that the fetus would engage with the stimuli in a manner consistent with postnatal visual literature that shows infants treat these sorts of stimuli as they do upright and inverted faces [4][5][6].…”
Section: Conceptualizationmentioning
confidence: 80%
“…However, using equation 2 from [3], as used by Reid et al [1], and the actual maternal tissue thickness for each subject, we calculate that 10 fetuses had intrauterine illuminances below the (admittedly arbitrary) 10 lx threshold suggested as the minimum for fetal vision [3] (see our R code). Furthermore, the authors did not code whether fetuses had their eyes open, a measure that three of them had recommended in an earlier review [4]. One of the authors also previously reported that 32-36-week-old fetuses opened their eyes 1.88-6.50 times per 10 minutes (Table 9.2 in [5]).…”
Section: Methodological Problems In a Study Of Fetal Visual Perceptionmentioning
confidence: 99%